Pelatihan Pengembangan E-Modul Flipbook: Mewujudkan Pembelajaran Digital yang Menarik dan Interaktif - Ni Nyoman Putri Nursanti; Reni Kartini Kristin Dian Yunianti; Intan Metrayani Sidauruk; Ashari Ramlan (PASAI : Jurnal Pengabdian kepada Masyarakat, 2026)
Digital transformation requires teachers not only to operate technology, but also to design engaging materials that foster students' learning interest. In practice, most teachers and pre-service teacher students still rely on printed modules and static PDF files because they lack the skills to operate flipbook-creation platforms. This community service program aimed to improve the ability of teachers and pre-service teacher students to develop flipbook e-modules in order to realize attractive and interactive digital learning, and to examine the training's effectiveness in strengthening that ability. The program was conducted online in June 2026 through a participatory training method with three stages, namely preparation, implementation, and evaluation, using a hands-on approach accompanied by intensive mentoring. Participants consisted of 28 teachers and pre-service teacher students selected purposively. Evaluation employed three instruments, namely pre-test and post-test of ability, e-module product assessment, and a participant satisfaction questionnaire, which were analyzed descriptively. The results showed improvement in participants' ability, indicated by an increase in the average score from 59.3 in the pre-test to 82.1 in the post-test, a gain of 22.8 points or a 38.4% improvement. The average e-module product score reached 84.6 in the good category, while participant satisfaction reached 92.1%. These findings indicate that the online training effectively shifted participants' orientation from technology users toward designers of attractive, interactive, and reflective digital learning. Sustained mentoring and institutional support are recommended to ensure classroom implementation.